A high-efficiency and low-cost AEE polyurethane chemo-sensor for Fe3+ and explosives detection. Issue 47 (21st November 2018) - Wang, Kun; Lu, Hao; Liu, Beibei; Yang, Jiping
Graphical abstract: Highlights: The modified polyurethane containing 0.13% TABDAA in soft segments was synthesized. The product polyurethane exhibited aggregation enhanced emission behavior. The AEE polyurethane showed high selectivity and sensitivity to Fe 3+ ion. The polyurethane solution can effectively detect explosives, especially for PA. Abstract: An aggregation enhanced emission (AEE) polyurethane named STMPU-211 containing 0.13% mole concentration of 4, 4′-((1Z, 3Z)-1, 4-diphenylbuta-1, 3-diene-1, 4-diyl) dibenzaldehyde (TABDAA) in the soft segments was synthesized and proved to be sensitive to Fe 3+ and nitroaromatic explosives. The fluorescence of the AEE polyurethane was reduced in the presence of Fe 3+, and almost quenched when 5000 μM Fe 3+ was added. Meanwhile, the fluorescence intensity of STMPU-211 solution in DMF/water mixture was decreased when explosives like 2, 4, 6-trinitrophenol (PA) and 3-nitro-1, 2, 4-triazol-5-one (NTO) were applied. Especially, the quenching coefficient KSV value of PA was 5.7 × 10 6  M −1, confirming that the polyurethane STMPU-211 could be a highly sensitive sensor for the detection of PA. Therefore, AEE polyurethanes with low concentration of TABDAA have promising applications in biological probe, environment monitoring and antiterrorism fields.